Legal Responsibility of PT Pembangunan Sabang Mandiri (Perseroda) Over the Assets and Liabilities of a Regional-Owned Enterprise Following a Change in Legal Form - Putri Cahaya Alyfia; Muhammad Insa Ansari; Teuku Ahmad Yani (Graha Primera Saintifika, 2026)
The transformation of a Regional Owned Enterprise (BUMD) from a Regional Company (Perusahaan Daerah) into a Regional Limited Liability Company (Perseroda) reflects the implementation of Good Corporate Governance, mandated by Article 402(2) of Law No. 23 of 2014 on Regional Government and operationalized through Sabang City Qanun No. 3 of 2020, which converted the Sabang Regional Development Company (PDPS) into PT Pembangunan Sabang Mandiri (Perseroda). This change entails the transfer of all assets and liabilities to the successor entity, yet in practice remains incomplete, raising questions of successor liability and creditor protection. This study analyses the Perseroda's legal liability for assets and liabilities arising from the transformation, the limits of such liability, and the legal protection of creditors. Using an empirical juridical method with a socio-legal approach, it draws on literature, legal documents, and interviews, analyzed qualitatively. The findings show that, under Article 7(1) and (3) of the Qanun, the transfer follows the principles of continuity of legal entity and universal succession, whereby all rights, obligations, assets, and legal relationships of the PDPS pass by operation of law to the Perseroda, which therefore bears full responsibility for them. Creditor protection remains secured, as pre-existing legal relationships are not extinguished and claims may be enforced against the successor. Empirically, however, the transfer lacks complete administrative and juridical settlement: inadequate inventory and verification, incomplete documentation, and ambiguous legal status of certain assets and obligations render both principles sub-optimally implemented, risking legal uncertainty. The study recommends comprehensive reorganization through inventory, verification, and clarification of asset status; clearer liability limits under Article 7 of the Qanun; and stronger creditor-protection mechanisms to ensure legal certainty.